2014
DOI: 10.1016/s1473-3099(14)70952-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of empirical antibiotic therapy optimisation in six hospitals: an observational cohort study

Abstract: Summary Background Modification of empirical antimicrobials when warranted by culture results or clinical signs is recommended to control antimicrobial overuse and resistance. We aimed to assess the frequency with which patients were started on empirical antimicrobials, characteristics of the empirical regimen and the clinical characteristics of patients at the time of starting antimicrobials, patterns of changes to empirical therapy at different timepoints, and modifiable factors associated with changes to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
93
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(98 citation statements)
references
References 27 publications
3
93
1
1
Order By: Relevance
“…It is evident that optimal antimicrobial use is linked with collection of cultures before prescribing the antimicrobial. 24 Another study demonstrated that timely bacteriological results are connected with decrease time to start effective therapy and reduction of 6 days in hospital stay. 25 By implementing this practice, a large number of inappropriate and unnecessary antibiotics could be avoided.…”
Section: Discussionmentioning
confidence: 99%
“…It is evident that optimal antimicrobial use is linked with collection of cultures before prescribing the antimicrobial. 24 Another study demonstrated that timely bacteriological results are connected with decrease time to start effective therapy and reduction of 6 days in hospital stay. 25 By implementing this practice, a large number of inappropriate and unnecessary antibiotics could be avoided.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported that the implementation of antibiotic/ sepsis bundles in patients with a sepsis code was associated with increased Clostridium difficile infection rates (5). Here is where diagnostic tests have an important role and a policy of antimicrobial stewardship focusing on reduced exposure to broad-spectrum antibiotic needs to be implemented (6).…”
mentioning
confidence: 99%
“…In addition, 20% of these patients were already on antibiotics before presentation and all of them have short hospital arrival times. As described in demography, the intervention focused on patients with different levels of severity-of-illness (38% with infection, 57% with severe sepsis and 4% with septic shock), being patients with septic shock or organ dysfunction a small proportion (6). Moreover, time to initiation of appropriate antibiotic prescription was not reported, but due to the low rate of resistances in the Netherlands, it was expected to be small, in contrast with other geographical regions with spread rate of resistances, particularly in Enterobacteriaceae.…”
mentioning
confidence: 99%
“…Moreover, in retrospective analyses it could be shown that in only about 30% of patients did the initial calculated antibiotic therapy actually encompass the pathogen, and de-escalation of therapy was only undertaken in a third of patients [127][128][129][130][131][132][133]. Combining broad-spectrum antibiotics simultaneously potentiates the selective pressure on pathogens and leads to increased development of resistance [134].…”
Section: Treatment Duration and Treatment Managementmentioning
confidence: 99%